1977
DOI: 10.2466/pms.1977.44.2.659
|View full text |Cite
|
Sign up to set email alerts
|

Visual Set and Anxiety in the Stroop Phenomenon

Abstract: The effects of a visual set, the Stroop phenomenon, and anxiety--as measured by the Spielberger State-Trait Anxiety Inventory--upon response latency were examined. Three variations of the set were presented, a color congruent with the response color, a color conflicting with the response color, or no color. Two response conditions were required, reading the color word or reporting the color in which the word was printed. "Reporting the color" had a significantly longer response latency than "reading the word" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
1

Year Published

1978
1978
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
3
1
Order By: Relevance
“…Given the paucity of studies of gender differences in response to "natural" stressors, only tentative conclusions are feasible. When examining personality differences, it has been found that subjects who are high in "trait anxiety" tend to show more interference (read more slowly) (Hochman, 1969;Jorgenson, 1977;Ray, 1979). In the present data, however, men were faster and less accurate than women in the low-anxiety condition while equally fast and still less accurate in the high-anxiety condition.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Given the paucity of studies of gender differences in response to "natural" stressors, only tentative conclusions are feasible. When examining personality differences, it has been found that subjects who are high in "trait anxiety" tend to show more interference (read more slowly) (Hochman, 1969;Jorgenson, 1977;Ray, 1979). In the present data, however, men were faster and less accurate than women in the low-anxiety condition while equally fast and still less accurate in the high-anxiety condition.…”
Section: Discussioncontrasting
confidence: 78%
“…Those who were most anxious about their impending examinations exhibited the most interference. She also suggests that the Stroop task could be used effectively as a measure of anxiety F~n a l l~, Jorgenson (1977) found that female students who scored high and low on trait anxiety showed more interference than those who scored medium on trait anxiety.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The size of the Stroop effect was not affected significantly by personality factors, which is consistent with the findings of Jensen (1965a), although there was a nonsignificant trend for high P scorers to show a larger Stroop effect than low P scorers. It may be relevant that Jorgenson (1977) reported a curvilinear relationship between Stroop interference and anxiety level (measured by the Spielberger, 1970, State-Trait Anxiety Inventory). Low-and high-anxiety females showed a larger Stroop effect than did medium-anxiety females.…”
Section: Discussionmentioning
confidence: 99%